Rancang Bangun Aplikasi Pengintai Aktifitas Komputer Menggunakan Layanan Cloud To Device Messaging (C2DM) Pada Smartphone Android - Azwar Anas; Anjik Sukmaaji; Teguh Sutanto (Jurnal Sistem Informasi Universitas Dinamika, 2012)
Computer ownership is increasing makes users more or less will affect the number of users who interact with it. Based on the results of research conducted National Center Education Statistics (NCES, 2003). Segmentation of Internet use in adolescents in this age range as much as 42 use it to complete school assignments, while 38 percent use email or chat facilities which includes playing games online, and 22 percent subsequently use the internet for browsing and searching for information. But not all the content containing educational information, and also a lot of negative information that is not compliant accessible to children. To solve this problem it created a system that can monitor the activities of users such as children when accessing the computer in realtime using the Cloud To Device Messaging Service (C2DM) on Android smartphones by parents. Given the android smartphone is also a handset that is able to always connect to the Internet for realtime data synchronization is different from ordinary mobile phones to be done manually. Given this system, the role of parents to monitor their children when accessing the computer is not overlooked. Keyword: Android, C2DM, Monitors Computer Activity, Keylogger